Exposure to copper nanoparticles impairs ion uptake, and acid and ammonia excretion by ionocytes in zebrafish embryos. (December 2020) - Lee, Chih-Ying; Horng, Jiun-Lin; Liu, Sian-Tai; Lin, Li-Yih
Abstract: The potential toxicity of copper nanoparticles (CuNPs) to early stages of fishes is not fully understood, and little is known about their effects on ionocytes and associated functions. This study used zebrafish embryos as a model to investigate the toxic effects of CuNPs on two subtypes of ionocytes. Zebrafish embryos were exposed to 0.1, 1, and 3 mg L −1 CuNPs for 96 h. After exposure, whole-body Na + and Ca 2+ contents were significantly reduced at ≥0.1 mg L −1, while the K + content had decreased at ≥1 mg L −1 . H + and NH4 + excretion by the skin significantly decreased at ≥1 mg L −1 . The number of living ionocytes labeled with rhodamine-123 had significantly decreased with ≥0.1 mg L −1 CuNPs. The ionocyte subtypes of H + -ATPase-rich (HR) and Na + /K + -ATPase-rich (NaR) cells were labeled by immunostaining and had decreased with ≥1 mg L −1 . Shrinkage of the apical opening of ionocytes was revealed by scanning electronic microscopy. Functional impairment was also reflected by changes in gene expressions, including ion transporters/channels and Ca 2+ -regulatory hormones. This study shows that CuNP exposure can impair two subtypes of ionocytes and their associated functions, including Na + /Ca 2+ uptake and H + /NH4 + excretion in zebrafish embryos. Graphical abstract: Image 1 Highlights: Waterborne CuNP impairs ion uptake, and acid and ammonia excretion by ionocytes in zebrafish embryos. Whole-body Na + and Ca 2+ contents were significantly reduced at ≥0.1 mg L −1 CuNP. H + and NH4 + excretion by the skin significantly decreased at ≥1 mg L −1 CuNP. The number of HR and NaR cells in yolk sac skin had decreased at ≥1 mg L −1 CuNP. Gene expressions of ion transporters/channels and Ca 2+ -regulatory hormones were influenced by CuNPs.